2006
DOI: 10.1111/j.1475-3995.2006.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the business cycle on bankruptcy probability

Abstract: Abstract:I combine two fields of research on default prediction by empirically testing a bankruptcy prediction function where unlisted firms are evaluated on the basis of both their financial statement analysis and the macroeconomic environment. This combination is found to improve the default prediction compared to financial statements alone. The GDP-gap, a production index and the money supply M1 in combination with some financial health indicators for individual firms are found to be significant predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
3
31
0
1
Order By: Relevance
“…Furthermore, the choice of one method over another is usually based on several heterogeneous criteria, such as data availability. Nevertheless, in recent years, some authors have shown the superiority of NNs relative to other techniques (Hol, 2006;Lee & Choi, 2013;Levy-Yeyati, Martínez Pernía & Schmukler, 2010;Mokhatab Rafiei, et al, 2011). In particular, du Jardin (2010) who uses more than 500 ratios taken from approximately 200 previous papers, shows that an NN-based model that uses a set of variables selected with a criterion specifically adapted to the network leads to better results than a set chosen with criteria used in the financial literature.…”
Section: Review Of Bankruptcy Prediction Modelsmentioning
confidence: 97%
“…Furthermore, the choice of one method over another is usually based on several heterogeneous criteria, such as data availability. Nevertheless, in recent years, some authors have shown the superiority of NNs relative to other techniques (Hol, 2006;Lee & Choi, 2013;Levy-Yeyati, Martínez Pernía & Schmukler, 2010;Mokhatab Rafiei, et al, 2011). In particular, du Jardin (2010) who uses more than 500 ratios taken from approximately 200 previous papers, shows that an NN-based model that uses a set of variables selected with a criterion specifically adapted to the network leads to better results than a set chosen with criteria used in the financial literature.…”
Section: Review Of Bankruptcy Prediction Modelsmentioning
confidence: 97%
“…Hence, opposed to past results (e.g., Krüger 2011; Detotto and Otranto 2012), we found no support for the case of Sweden; similarly, we could not directly link changes in the overall bankruptcy volume to macro-economic variation (see Appendix). Several studies have attempted to assess the link between bankruptcies and the business cycle (Levy and Bar-niv 1987;Hol 2007). However, efforts to link variations in bankruptcies to the cycle might have to control for or consider the fact that the total number of bankruptcies will always consist of bankruptcy frauds.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In an upturn, business exits and bankruptcies are claimed to decrease and vice versa. Overall, the empirical literature provides evidence of the relation between exit rates and bankruptcy volume and the business cycle at both the micro-level (e.g., Everett and Watson 1998;Bhattacharjee et al 2009) and the macro-level (Levy and Bar-Niv 1987;Balcaen and Ooghe 2006;Hol 2007). It would be surprising if crime rates were immune to the business cycle (Cook and Zarkin 1985).…”
Section: Data and Variablesmentioning
confidence: 99%
“…All fifty companies of non-financial sector are discussed in that results and the study of the research guide us that the Altman Z-Score and Abbas model both are significantly difference between expected financially failed and non failed companies in 2007. But in 2008, 2011and 2012 that are not significant.…”
Section: Discussionmentioning
confidence: 84%